Conceptual Model of Accelerating the Adoption of Small and Medium Industries in Implementing Industry 4.0 with the Lean Manufacturing Approach - Muizzullah, Risma Fattahatin; Komarudin, K; Hidayatno, Akhmad (Universitas Muhammadiyah Surakarta, 2019)
Purpose: Making a conceptual model that can provide the policy strategy in accelerating the adoption of industry 4.0 in Small and Medium Industries (SMI) using lean manufacturing approach.Methodology: Using the conceptualization process in system dynamics methodology to get causal relation among the factors which can affect the implementation of industry 4.0 in Small and Medium Industries. The lean management approach was used to get these factors and compile their causal relation with readiness of industry 4.0 as a conceptual model.Result: A conceptual model that shows important variables and its relationship structure that could be used in better understanding the adoption proceeses of Industry 4.0 technology. Several interconnection loops are identified in the conceptual model that can be the basis for better policy design by focusing on adjusting one or more variables in the loops, in the manner of understand the relationships that occur in the conceptual model, the government can predict the outcome of the policy to be implemented. Applications/Originality/Value: Providing a better understanding of adoption process for better policymaking by the Indonesian government, particularly the Ministry of Industry, to encourage the readiness of industry 4.0 implementation in Small and Medium Industries.